Against the spread [videorecording (DVD)] - Cole, Mitchell; Cole, Mitchell; Trovato, Bobby; Skinner, Jake (Well Go USA Entertainment, 2025)
In the rural South, a down-and-out gambling addict reignites a deep-rooted rivalry with a ruthless loan shark to finance his nimwitted nephew's half-baked scheme.